A Princess of Roumania - Park, Paul (Tom Doherty Associates, LLC, 2005)
This a truly magical tale, full of strangeness, terrors and wonders. ,Many girls daydream that they are really a princess adopted by commoners. In the case of teenager Miranda Popescu this is literally true$1! =s
Keywords: Fiction